Tablet 27 Feb 1913 to Graham Pole (Secretary General Theosophical Society) - Abdul-Bahá (1913)
Tablet to Graham Pole, Secretary General of the Theosophical Society (Scotland), from France, 27 Feb 1913. Original translation by Ahmad Sohrab.
Typed from the original in the Edinburgh Archives.
Keywords: Edinburgh, Scotland; Graham Pole; Scotland; Theosophical Society; United Kingdom; `Abdu'l-Bahá, Writings and talks of